If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4 = 6z + -8z Combine like terms: 8 + -4 = 4 4 = 6z + -8z Combine like terms: 6z + -8z = -2z 4 = -2z Solving 4 = -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. 4 + 2z = -2z + 2z Combine like terms: -2z + 2z = 0 4 + 2z = 0 Add '-4' to each side of the equation. 4 + -4 + 2z = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2z = 0 + -4 2z = 0 + -4 Combine like terms: 0 + -4 = -4 2z = -4 Divide each side by '2'. z = -2 Simplifying z = -2
| k^3+2k^2-10k-20=0 | | 7(x+2)=7x+10 | | z^4-26z^2+25=0 | | 5x-10-2=13 | | 1/2x16=0 | | p^(2/3)+p^(1/2) | | 3x-7+5=16 | | (x^2-81)/(x^2-6x-27)*(x+3)/x | | 98x+456= | | x^3-4x=85008 | | 250=(50-3)+x | | s=2x+t/r | | x/5-x=1/5 | | 0.5y=30 | | -6(x-2)+4(8x-12)=68 | | 6ln(3x)=12 | | -6(x-2)-4(8x-12)=68 | | 3x-2=7x+8 | | 4(-6+x)=5x+1/4 | | h=4a-3 | | 1/6-18/12 | | 7-3(5t-7)=67 | | 5x^2y^4-80x^4y^2=0 | | 1=23*t+2-1-2+1-23*t+2*t-1*t | | 23*t+2-1-2+1-23*t+2*t-1*t=1 | | 2w^2-5w-88=0 | | 2x-6+5=11 | | 3x-1-4=1 | | (-5y^3/8y^4)*(64y^6/25y) | | 3056890000-15000000x=3000000 | | 2n^3-32n=0 | | 1/3(9k-6)=7 |